Robert Frost, America's poet. - Faber, Doris, 1924-; Frame, Paul, 1913-1994 (Englewood Cliffs, N.J., Prentice-Hall, 1964)
Brief biography of the New England farmer and teacher who became one of America's best known poets.
Keywords: Frost, Robert, -- 1874-1963 -- Juvenile literature; Frost, Robert, -- 1874-1963.; Poets, American -- 20th century -- Biography -- Juvenile literature; Poets, American